2021
DOI: 10.1007/s00122-021-03816-z
|View full text |Cite
|
Sign up to set email alerts
|

Stripe rust resistance gene Yr34 (synonym Yr48) is located within a distal translocation of Triticum monococcum chromosome 5AmL into common wheat

Abstract: Key messageThe stripe rust resistance geneYr34 was transferred to polyploid wheat chromosome 5AL from T. monococcumand has been used for over two centuries.Wheat stripe (or yellow) rust, caused by Puccinia striiformis f. sp. tritici (Pst), is currently among the most damaging fungal diseases of wheat worldwide. In this study, we report that the stripe rust resistance gene Yr34 (synonym Yr48) is located within a distal segment of the cultivated Triticum monococcum subsp. monococcum chromosome 5AmL translocated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 58 publications
(93 reference statements)
0
31
0
Order By: Relevance
“…LongReach Lancer (Supplementary Data 1). Previous studies have reported introgressions on wheat chromosomes 5AL and 7AL from T. monococcum 41 and T. boeoticum 42 , respectively, although the introgressed regions differ. In contrast, the introgression on chromosome 1AS has been described for cv.…”
Section: Detection Of Nine Introgressions In 10 Wheat Rqasmentioning
confidence: 90%
See 1 more Smart Citation
“…LongReach Lancer (Supplementary Data 1). Previous studies have reported introgressions on wheat chromosomes 5AL and 7AL from T. monococcum 41 and T. boeoticum 42 , respectively, although the introgressed regions differ. In contrast, the introgression on chromosome 1AS has been described for cv.…”
Section: Detection Of Nine Introgressions In 10 Wheat Rqasmentioning
confidence: 90%
“…We identified putative introgressions as regions with decreased coverage of reads from the progenitor species of the wheat subgenomes; that is, for a genomic window, the proportion covered by reads is decreased (Methods). Triticum urartu (2n=2x=14, A u ) and Aegilops tauschii (2n=2x=14, D) are the donors of the A and D subgenomes of wheat [20][21][22] , respectively, whereas the donor of the B subgenome is either not known yet or extinct 23 . Aegilops speltoides (2n=2x=14, S) is the most closely related remnant taxon to the wheat B subgenome donor [23][24][25] .…”
Section: Detection Of Nine Introgressions In 10 Wheat Rqasmentioning
confidence: 99%
“…LongReach Lancer (Supplementary Data 1 ). Previous studies have reported introgressions on wheat chromosomes 5AL and 7AL from T. monococcum 41 and T. boeoticum 42 , respectively, although the introgressed regions differ. In contrast, the introgression on chromosome 1AS has been described for cv.…”
Section: Resultsmentioning
confidence: 90%
“…This observation is consistent with findings of introgressions from T. monococcum in bread wheat cv. Mediterranean 41 released in 1837. We hypothesise that the introgressions found in old cultivars resulted from spontaneous natural interspecific crosses that were subsequently selected.…”
Section: Discussionmentioning
confidence: 99%
“…T . monococcum harbours several valuable rust resistance genes, including the leaf rust resistance genes LrTM16 (Sodkiewicz and Strzembicka, 2008) and Lr63 (Kolmer and Anderson, 2010); the stripe rust resistance loci QYrtm.pau‐2A and QYrtb.pau‐5A (Chhuneja et al ., 2008) and Yr34 (Chen et al ., 2021); and the stem rust resistance genes Sr21 (Chen et al ., 2015; The, 1973), Sr22 (Gerechter‐Amitai et al ., 1971), Sr35 (McIntosh et al ., 1984), SrTm4 (Briggs et al ., 2015) and Sr60 and SrTm5 (Chen et al ., 2018a).…”
Section: Introductionmentioning
confidence: 99%